2012
DOI: 10.4244/eijv8i3a58
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomised trial of transapical transcatheter aortic valve implantation vs. surgical aortic valve replacement in operable elderly patients with aortic stenosis: the STACCATO trial

Abstract: Given the limitations of a small prematurely terminated study, our results suggest that a-TAVI in its present form may be associated with complications and device success rates in low-risk patients similar or even inferior to those found in high-risk patients with aortic valve stenosis. This will probably change in the near future with improved catheter based devices and better pre-procedural assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(121 citation statements)
references
References 19 publications
4
109
1
7
Order By: Relevance
“…Similar findings were observed in the PARTNER 2 study in intermediate‐risk patients, with hazard ratio 1.55 (95% confidence interval, 1.23–1.96), P <0.001 12. A much smaller prospective randomized trial of transapical TAVR versus SAVR in operable patients (the STACCATO trial) was stopped early because of a higher complication rate in the transapical TAVR arm, specifically death and stroke 49. Furthermore, health status improvements using the Kansas City Cardiomyopathy Questionnaire at 30 days in the PARTNER 2 study were greater with TAVR compared with SAVR, but only in patients who underwent transfemoral TAVR 22.…”
Section: Do Clinical Trials Of Tavr In Low‐risk Patients Herald the Esupporting
confidence: 69%
“…Similar findings were observed in the PARTNER 2 study in intermediate‐risk patients, with hazard ratio 1.55 (95% confidence interval, 1.23–1.96), P <0.001 12. A much smaller prospective randomized trial of transapical TAVR versus SAVR in operable patients (the STACCATO trial) was stopped early because of a higher complication rate in the transapical TAVR arm, specifically death and stroke 49. Furthermore, health status improvements using the Kansas City Cardiomyopathy Questionnaire at 30 days in the PARTNER 2 study were greater with TAVR compared with SAVR, but only in patients who underwent transfemoral TAVR 22.…”
Section: Do Clinical Trials Of Tavr In Low‐risk Patients Herald the Esupporting
confidence: 69%
“…Less encouraging data comes from the STACCATO Trial [16]. This study was designed a randomized prospective study to compare results of conventional surgery and trans-apical catheter based aortic valve implantation and enrolled a population of 34 TAVI patients (mean age 80.2, Log.…”
Section: Current Resultsmentioning
confidence: 99%
“…17 Randomized trials in high-risk populations have consistently shown an increased stroke rate with TAVR compared with SAVR. 3,18,19 A pooled meta-analysis of these randomized, clinical trials also demonstrated a significantly higher incidence of stroke with TAVR compared with SAVR (RR, 0.56; 95% CI, 0.36-0.88; P=0.01) at a mean follow-up of 99 weeks. 13 Despite some recent reports that have shown a reduction in stroke rate associated with TAVR, 6 the French Aortic National CoreValve and Edwards (FRANCE) II and Australian registries consistently demonstrate a 30-day stroke rate of 3.4% and 3.9% in the current era.…”
Section: Stroke Remains An Issue With Tavrmentioning
confidence: 99%